Welfare State Development in Central and Eastern Europe: A State of the Art Literature Review - Adascalitei, Dragos (Studies of Transition States and Societies, 2012)
The welfare states in Central and Eastern Europe (CEE) have undergone massive changes since the beginning of the 1990s. This paper reviews the literature on welfare state development in CEE in light of the theories that have been used to study advanced capitalist democracies. Its purpose is to critically assess the extent to which diﬀerent theories can explain changes in the welfare state during and after transition. It argues that until now two strands of literature have crystallised: institutionalism and actorcentred explanations. Institutionalists agree that welfare reforms are limited by the path dependence of the national welfare state structures though this framework is biased towards explaining stability. Recent literature seeks to overcome this bias by adding variables that traditionally belong to the actorcentred paradigm. This essay will argue that the gains from such an approach are exceeded by losses in the accuracy and parsimony of explanations. Further, in the actor-centred camp the welfare state is seen as a product of bargaining between various national and international actors. Yet the debate about who is responsible for the present welfare state arrangements is far from over. Unanswered questions revolve around the impact of political parties and ideologies on welfare reforms, the role of bureaucracies, the eﬃciency of international ﬁnancial institutions in advocating retrenchment and the precise mechanisms through which all the above actors defend their interests.